Short- and long-term changes in cognitive function after exercise-based rehabilitation in people with COPD: A pilot study. Issue 5 (3rd September 2021) - Rosenstein, Brent; Smyrnova, Anna; Rizk, Amanda; Escudier, Frédérique; Gagnon, Jean-François; Pepin, Véronique
Abstract: OBJECTIVES: To compare, in individuals with chronic obstructive pulmonary disease (COPD): 1) the effects of 12 weeks of continuous training at high intensity (CTHI), continuous training at the ventilatory threshold (CTVT) and high-intensity interval training (HIIT) on cognition; and 2) the maintenance of these effects at a 1-year follow-up. METHODS: Participants were randomized to CTHI, CTVT, or HIIT and underwent 12 weeks of three times weekly training on cycle ergometers. Training intensity and duration were set based on group allocation. At program completion, all participants were given standardized exercise recommendations from the exercise supervisors, but no active maintenance intervention was offered. Assessments were made at baseline (week 0), program completion (week 12) and 1 year after baseline (year 1). Cognition was assessed with a neuropsychological testing battery and the Montreal Cognitive Assessment (MoCA). RESULTS: In 36 participants (64% women, mean age: 67.5 ± 9 years) with moderate COPD (FEV1 : 59 ± 17% predicted), the 12-week effects of exercise training on cognition were small (Cohen's d z : −0.063-0.448). One exception was the Rey-O Complex Figure (copy), assessing visuoconstructive abilities, in which larger effects were detected, especially in participants with mild cognitive impairment at baseline (Cohen's d z = 1.122, 95% CI[0.406, 1.809]). Between intervention groups, results were heterogeneous. CTHI was the only group with medium-to-large effects in each cognitive domain. At year 1, gains and losses in cognition were seen across groups. CONCLUSION: In COPD, 12 weeks of exercise training led to small changes in cognition, with heterogeneity between exercise protocols and across cognitive domains.